Widening horizons and close encounters: overseas engagement and economic outcomes in southern Italy - Foxhall, Lin (Journal of Greek Archaeology, 2020)
This paper takes the first steps in a new direction on a much-studied theme, exploring how Late Bronze and Iron Age Italic societies in southern Italy, especially their elites, positioned themselves and operated within the wider networks through which they were connected. Here I will consider the economic consequences of engagement with these networks, with particular attention to the economic outcomes of interaction with Aegean visitors and cultures and the extent of their impact. I will argue that while the impact of interaction with Aegean culture was not insignificant, Italic elites may generally have been more concerned with and focused on local and regional interactions than on relationships with incomers from overseas and wider Mediterranean connectivity, even in the areas in which such engagement was most concentrated.